87 Leadership and management skills for new clinical oncology trainees – has a prescriptive approach resulted in poor compliance?. (3rd November 2019) - Charlton, Thomas; Cheah, Anita; Thakrar, Priya; Bailey, Emma; Thomas, Alex; Kitchen, Sian; Szram, Jo
Abstract : Background: Advances in cancer treatment continue at rapid pace, patient numbers are increasing and there is a significant workforce shortage. Strong leadership and management is required. Leadership and management features heavily in the RCR's 2016 Clinical Oncology (CO) Syllabus, however, there is limited scope for formal development in this area. The Spiral Leadership Toolkit (SLT) was introduced to help trainees practically develop these competencies during training. Based on the NHS Leadership Academy's Healthcare Leadership Model, it includes eight domains, e.g. finance and risk. Intervention: A pilot study involving all new South London CO ST3 trainees (September 2019). The objective was to complete at least two projects from the eight domains during ST3. To demonstrate compliance, trainees were advised to upload evidence onto their e-portfolios as part of ARCP (May 2019). A midpoint, cross-sectional survey was distributed to trainees after 6 months to understand how the SLT had been used and any challenges faced. Results: 14/15 (93%) trainees responded. Only 4/14 (29%) had used the SLT to complement their training. 7/14 (50%) trainees had included SLT in their Personal Development Plan (PDP). In terms of barriers, 9/12 (75%) felt that they had received neutral or limited support from their trust. 7/14 (50%) stated that they didn't have time to participate. Written comments included 'Another hoop to jump through' and a 'mandatory form filling exercise'. Conclusion: There has been a disappointing uptake with only a third of trainees using the SLT. Two major barriers include a lack of time and support from trusts. Half of trainees have included the SLT in their PDP, demonstrating a future intention to participate. It is clear that trainees are struggling to balance multiple commitments and that the SLT is being viewed by some as another 'tick box' exercise. Hopefully some trainees have found it a useful tool for developing vital skills.